Deconstructing Mythological Foundations of Ethnic Identities and Ethnic Group Formation: Albanian-Speaking and New Armenian Immigrants in Switzerland - Dahinden, Janine (My University, 2008)
Scholars generally agree that ethnicity often serves as a vehicle for mechanisms of social inclusion or exclusion and is interwoven with the structures of nation-states. This article aims to contribute to the ongoing debate about ethnicity and highlights the inherent dilemma of essentialism using two empirical case studies—Albanian-speaking migrants living in Switzerland and newly arrived Armenian migrants who left Armenia after independence in 1991. By directing attention to the processes of boundary construction, as well as to the relative and situational character of ethnicity, the paper shows how representations of collective ethnic identities are formed, transformed, reformulated or shifted to other representations of collective identities. By analysing the degree of reification of ethnic identities, it becomes clear that the ladder from 'soft' to 'hard' essentialisation has many steps. Furthermore, the case studies reveal that, in contemporary Switzerland, other categories are relevant for social exclusion or inclusion as well, mainly the type of residence permit and professional qualifications—categories which are also interwoven with ethnicity.
Keywords: Ethnicity; Albanian Migrants; Armenian Migrants; Switzerland; Social Exclusion